Pharmacokinetic and Pharmacodynamics of Sodium Diclofenac (Topical and IM) Associated with Laser Photobiomodulation on Skeletal Muscle Strain in Rats. (3rd March 2019) - de Paiva Carvalho, Rodrigo Leal; Leonardo, P. S. L. M.; Mendes, Gustavo Duarte; Lima, Fernanda Púpio Silva; Lima, Mário Oliveira; Marcos, Rodrigo Labat; Lopes-Martins, Rodrigo Alvaro Brandão
Abstract : Purpose . The practice of physical activities is considered a primary factor for the maintenance of good health status. However, exhaustive or unusual physical activities can lead to muscle injuries. Several treatments are used to recover muscle injuries; however, systemic NSAIDs often result in serious adverse events. In this study, we aimed to investigate the association of laser therapy (LLLT) and topical diclofenac, evaluating the kinetics of the drug and its pharmacodynamic effect in stretching-induced muscle injury in rats. Methods . Male Wistar rats weighing 200 g were randomized and divided into groups of 6 animals. Plasma concentrations of diclofenac were quantified by mass spectrometry at different times (15 min to 24 hours) in all animals. The laser energy used was 3 Joules (830 nm; 100 mW, 30s). Treated groups received diclofenac at the dose of 1 mg/kg IM or topically applied with or without laser therapy. The electric stimulation was used to study the functional status of the muscles. Results . After topical administration of diclofenac, the peak plasma concentration (t max) occurred for 30 minutes in the irradiated group and 4 hours in the nonirradiated group. The AUC (0-24 hs) was 442 (ng/h/mL -1 ) in the nonirradiated group and 712 (ng/h/mL -1 ) in the irradiated group. Conclusion . LLLT was effective to provide a significant improvement in functional patterns. Taken together, our results demonstrate the synergistic effect between LLLT and topical diclofenac in muscle injury induced by stretching in rats.